The role expectations of secondary school guidance counselors as viewed by administrators, teachers and counselors from selected public secondary schools in Region III - Moscoso, Raulito Ocampo 1941- (1978)
This study aimed to find out the perceptions of the role of secondary school guidance counselors among the school administrators, teachers, and guidance counselors as well as how these three groups prioritize certain students problems and how they deal with them. The descriptive survey method was used with the questionnaire, which was administered to 311 school personnel, as the major instrument in this study. It was revealed that the respondents have varying degrees of concensus with regards to some specific functions and their perceptions of the secondary school guidance counselor. Secondary school administrators, teachers, and guidance counselors tend to prioritize student problems that need attention similarly. There is a need for more professional training in guidance and counseling for the guidance counselor respondents. Lack of professionally-trained guidance personnel also proved to be a problem of public secondary schools, especially the barangay high schools.
Appendices: leaves 125-189
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: Student counselors; Personnel service in education -- Philippines